Decifrare le proteine: un fondamentale aiuto dall’Intelligenza Artificiale - Chioccioli, Matteo (Chimica nella Scuola, 2023)
Proteins are key biological macromolecules which play a pivotal role both in living organisms and in chemical and pharmaceutical research. One of the major obstacles in understanding these polymers has long been the experimental determination of their tridimensional structures. This field of research has recently drawn the attention of the major Artificial Intelligence (AI) companies which have developed highly sophisticated algorithms aimed at solving this scientific problem. This article underlines the fact that these AI programs not only have been able to predict the 3-D structures of every known protein found in nature, in the last two years, but also to create artificial proteins from scratch. As a consequence, this will greatly speed up research ranging from designing new drugs to tackling technological and energetic challenges.